1987
DOI: 10.1288/00005537-198701000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocytic antigens in autoimmune sensorineural hearing loss

Abstract: Susceptibility to many autoimmune diseases is associated with inheritance of certain Human Leukocytic Antigens (HLA), determinants which have become diagnostic or prognostic markers. In this study of HLA antigen frequencies among patients with autoimmune sensorineural hearing loss, 39 patients with this otologic disorder were typed for HLA-A, B, C, and DR antigens. A significant increase of Cw7 occurred in 51% of patients compared to 21% of 627 matched controls (relative risk, 3.95). Trends towards increased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 11 publications
1
17
0
1
Order By: Relevance
“…These differences did not reach statistical significance and the study of additional patients is needed. Higher frequencies of these HLA types in ASNHL subjects were not observed in studies by other groups (27)(28)(29)(30)(31)(32)(33).…”
Section: Hla Typing Of Asnhl Patientsmentioning
confidence: 52%
See 1 more Smart Citation
“…These differences did not reach statistical significance and the study of additional patients is needed. Higher frequencies of these HLA types in ASNHL subjects were not observed in studies by other groups (27)(28)(29)(30)(31)(32)(33).…”
Section: Hla Typing Of Asnhl Patientsmentioning
confidence: 52%
“…This implies that CD8 ϩ T cells may be sufficient to account for inner ear autoimmunity. Indeed, several studies have implicated higher frequencies of a variety of HLA class I alleles in ASNHL including A2, A25, B18, B35, B39(B16), B41, Bw16, Cw4, Cw5, and Cw7 (27)(28)(29)(30). The increased frequencies of numerous different class I alleles in ASNHL implies that multiple proteins and their derived peptides may be involved in inner ear-specific self-recognition.…”
Section: Discussionmentioning
confidence: 99%
“…This has been done, for example, for the association between HLA-B27 and ankylosing spondylitis. Since the first report in 1973 of a high association of HLA-B27 with ankylosing spondylitis [5], some 30 reports from different laboratories have emerged, confirming the same finding in every population studied [7], If we scrutinize the data in table 5. then we see that HLA-Cw7 was associated with Meniere's disease [45] and autoimmune sensorineural hearing loss [43], respectively. Xenellis et al [45] reported that 75% of their 41 patients with Meniere's disease had HLA-Cw7.…”
Section: Discussionmentioning
confidence: 79%
“…The frequency of this antigen in normal control subjects was not given. Bowman and Nelson [43] found that 51% of their 39 patients with clinically diagnosed autoimmune sensori neural hearing loss had Cw7, whereas in normal controls the antigen frequency was 21%. We did find that Cw7 was present in 47.5% of our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation